Reconfigurable Optical Directed Logic Circuits Based on Mode Division Multiplexing Technology - Mingrui Yuan; Yiyang Li; Huifu Xiao; Xudong Zhou; Pengfei Cao; Lin Cheng; Guanghui Ren; Qinfen Hao; Jiuzhi Xue; Arnan Mitchell; Yonghui Tian (IEEE Photonics Journal, 2023)
Reconfigurable optical directed logic circuits (RODLC) aim to perform arbitrary logic operations using the optical switch network, in which the electrical signals regarded as the logic operands are applied to the optical switch to control the propagation of light over time, and the logic operation results are obtained at the output ports of the optical switch network in the form of light. In this paper, a novel RODLC is proposed and experimentally demonstrated by utilizing an optical switch array with the prosperous optical mode division multiplexing (MDM) technology to perform arbitrary logic functions. As a proof of concept, a RODLC with two optical mode (de)multiplexers and twelve thermo-optic microring resonators on a silicon-on-insulator substrate is fabricated based on standard microfabrication technology. To demonstrate its reconfigurability to perform arbitrary logic functions, eight logic operations: NOT, AND, NAND, OR, NOR, XOR, XNOR, as well as one combination operation of four-operand, with the operation speed of 10 Kbps are successfully implemented as examples. The demonstrated RODLC characterized with reconfigurability, scalability, and ability for large-scale integration, will contribute to the flourishing development of optical computing and information processing in large-scale optical hybrid integrated circuits.